Forensic analysis of gasoline on burnt carpet by gas chromatography technique - Samri, Mohamad Abdin Shakirin (Universiti Sains Malaysia, 2016)
The presence of ignitable liquid residues is important to confirm the involvement of arson attack in a fire scene. During forensic investigation, the chances of finding sufficient ignitable liquid remained in an unaltered form after a fire is relatively low. Therefore, this study focused on the effect of different fire extinguishing methods in influencing the possibility of detection of gasoline residues on burnt carpets. In this study, carpets doused with gasoline were burnt to simulated fire condition followed by five different fire extinguishing methods, namely ABC powder fire extinguisher, water, cloth, sand and also on self-extinguishment. Through gas chromatography (GC) examination, the profiles of gasoline residue from simulated conditions were generated. No interfering product due to the different extinguishing methods was observed. The profiles of gasoline were still observable when compared with the profile of neat gasoline. However, the gasoline residue showed some degree of chromatographic swift possibly due to loss of lighter hydrocarbon compounds. Principal Component Analysis provided an objective characterisation but it allowed only the differentiation of samples subjected to water extinguishing method from the others. In conclusion, the study enabled the detection of gasoline on burnt carpets but the use of varying fire extinguishing methods did not influence the possibility to detect gasoline on burnt carpets. The findings suggested that residues of gasoline could still be detected although subjected to extinguishment unless the gasoline was totally burnt during a fire.